Analysis of budget spending and its affect on Jambi Government performance - Heriberta Heriberta; Aulia Tasman; Yanilia Yanilia (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2018)
The purpose of this research are: 1) to investigated the tendency of budget absorption to regional working units (SKPD in Indonesian) expenditure in the provincial government of Jambi; 2) to analyze factors that influence the SKPD’s budget absorption in the provincial government of Jambi; 3) to examine the effect of budget absorption on agency performance in the provincial government of Jambi. The data used in the research are secondary data in the form of budget realization reports, and primary data by using questionnaires. The population in this research are all SKPD in the environment of the provincial government of Jambi. The data analysis tools used in this research is Partial Least Square (PLS). The research finding shows that 1) all SKPD in the environment of the provincial government of Jambi tend to be delayed in budget absorption. About 82.61% SKPD tend to be delayed in budget absorption of personnel expenditure. All SKPD tend to be delayed in budget absorption of goods and services expenditure, and 43.90% SKPD tend to be delayed in budget absorption of capital expenditure; 2) budget planning and budget execution are the factors that affect the budget absorption significantly, while capacity of human resources has no effect on the budget absorption, and 3) the budget absorption has a positive and significant impact on the agency performance in the provincial government of Jambi